Potential Of Vitamin C And Total Acid As Antioxidants Of Rosella Kombucha With Different Fermentation Times - Winandari, Ovi Prasetya; Widiani, Nurhaida; Kamelia, Marlina; Rizki, Erika Puspita (Universitas Labuhanbatu, 2022)
Germplasm which is abundant in Indonesia, 23% of which are medicinal plants. One of the medicinal plants is rosella because it contains various compounds that are proven to be natural antioxidants, anticancer, antihypertensive, laxative, and natural antidiuretic. Herbal medicines are often consumed as functional drinks. Rosella can be processed into functional drinks, one of which is kombucha. The length of fermentation of kombucha can affect the content in it. This type of research is descriptive quantitative. The treatments given were 3, 6, 9, and 12 days of fermentation. Parameters measured included vitamin C content, total lactic acid, antioxidant activity, total microbes, and pH. The results showed that the highest vitamin C content was 0.0528 mg/mL on days 3 and 6, the highest total lactic acid was 1.7250% on day 12, the best antioxidant activity was on day 9 with a very strong category, the highest total bacteria was 5.96x107 CFU/mL on day 12 12th, the highest total yeast 11.54x106 Log CFU/mL on the 6th day, the highest pH of 2.70 on the 3rd day.Keywords: kombucha, rosella, vitamin C, antioxidant